Acute disseminated encephalomyelitis (ADEM) following COVID-19 vaccination: A systematic review. (May 2023) - Nabizadeh, Fardin; Noori, Maryam; Rahmani, Shayan; Hosseini, Helia
Highlights: It is not clear that ADEM could be a potential complication of COVID-19 vaccination based on the current evidence. This rare condition should not trigger stopping the mass vaccination programs since the only way to eradicate the current pandemic of COVID-19 is the vaccination. Most of the ADEM developed after the first dose of vaccination. Abstract: Background: Although global vaccination against COVID-19 infection has its excellence, potential side effects are yet of concern. Several lines of evidence have proposed ADEM occurrence after SARS-CoV-2 infection. Moreover, a large number of case reports and case series have also suggested the casual association between ADEM and COVID-19 vaccination. To better understand the development of ADEM following COVID-19 vaccination and its potential association, we aimed to systematically review ADEM cases reported after COVID-19 vaccination. Methods: We conducted a comprehensive systematic search using three databases including PubMed, Scopus, and Web of Science. Studies that reported ADEM after COVID-19 vaccination were eligible to include in our study. Observational studies, case reports, and case series which reported cases of ADEM with sufficient detail to confirm clinical diagnosis following COVID-19 vaccination were eligible to enter our study. Results: Twenty studies were included in our systematic review after the abstract and full-text screening with a total of 54 cases. Among included patients, 45 (85.1 %) developed ADEM after the first dose of the COVID-19 vaccine, and seven (12.9 %) cases experienced ADEM after the second dose. The median time interval between vaccination and neurological symptoms was 14 days which ranged from 12 h to 63 days. Twelve (22.2 %) patients experienced symptoms of muscle weakness, ten (18.5 %) presented unconsciousness, nine (16.6 %) patients had urinary complaints, nine (16.6 %) had visual impairments, and five (9.2 %) experienced a seizure. After treatments, four (13.8 %) patients died. Forty-six patients had clinical improvement (85.1 %), also improvement in brain MRI was observed among 44 (81.4 %) patients. Conclusion: In conclusion, it is not clear that ADEM could be a potential complication of COVID-19 vaccination based on the current evidence and further studies are needed. However, this rare condition should not trigger stopping the mass vaccination programs since the only way to eradicate the current pandemic of COVID-19 is to extend the number of immunized people.